Integrins modulate Sog activity in the Drosophila wing. - Araujo, H.; Negreiros, E.; Bier, E. (Development, 2003)
Morphogenesis of the Drosophila wing depends on a series of cell-cell and cell-extracellular matrix interactions. During pupal wing development, two secreted proteins, encoded by the short gastrulation (sog) and decapentaplegic (dpp) genes, vie to position wing veins in the center of broad provein territories. Expression of the Bmp4 homolog dpp in vein cells is counteracted by expression of the Bmp antagonist sog in intervein cells, which results in the formation of straight veins of precise width. We screened for genetic interactions between sog and genes encoding a variety of extracellular components and uncovered interactions between sog and myospheroid (mys), multiple edematous wing (mew) and scab (scb), which encode betaPS, alphaPS1 and alphaPS3 integrin subunits, respectively. Clonal analysis reveals that integrin mutations affect the trajectory of veins inside the provein domain and/or their width and that misexpression of sog can alter the behavior of cells in such clones. In addition, we show that a low molecular weight form of Sog protein binds to alphaPS1betaPS. We find that Sog can diffuse from its intervein site of production into adjacent provein domains, but only on the dorsal surface of the wing, where Sog interacts functionally with integrins. Finally, we show that Sog diffusion into provein regions and the reticular pattern of extracellular Sog distribution in wild-type wings requires mys and mew function. We propose that integrins act by binding and possibly regulating the activity/availability of different forms of Sog during pupal development through an adhesion independent mechanism.